2018
DOI: 10.3390/foods7090132
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Fresh Meat from Several Species Based on Free Amino Acid and Biogenic Amine Contents during Chilled Storage

Abstract: This paper studies the changes that occur in free amino acid and biogenic amine contents of raw meats (beef, pork, lamb, chicken and turkey) during storage (2 °C, 10 days). The meat cuts samples were harvested from a retail outlet (without getting information on the animals involved) as the following: Beef leg (four muscles), pork leg (five muscles), lamb leg (seven muscles), turkey leg (four muscles), and chicken breast (one muscle). Meat composition varied according to meat types. In general, pH, microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 47 publications
7
76
4
Order By: Relevance
“…Alanine was the most abundant FAA, which reached 13.78 ± 0.44 mg/100 g muscle on average for all the five dietary treatments. This is in agreement with literatures, which reported that alanine had the highest concentration (18.70 mg/100 g) (Triki, Herrero, Jimenez‐Colmenero, & Ruiz‐Capillas, ) and accounted for the greatest percentage (13.25‐14.49%) of total FAAs (Chang et al., ) in fresh pork meat. The total FAAs determined in the present study were between 69.35 and 75.63 mg/100 g, which is consistent with reports that 77.50 mg/100 g of total FAA was determined in pork leg cuts (Triki et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Alanine was the most abundant FAA, which reached 13.78 ± 0.44 mg/100 g muscle on average for all the five dietary treatments. This is in agreement with literatures, which reported that alanine had the highest concentration (18.70 mg/100 g) (Triki, Herrero, Jimenez‐Colmenero, & Ruiz‐Capillas, ) and accounted for the greatest percentage (13.25‐14.49%) of total FAAs (Chang et al., ) in fresh pork meat. The total FAAs determined in the present study were between 69.35 and 75.63 mg/100 g, which is consistent with reports that 77.50 mg/100 g of total FAA was determined in pork leg cuts (Triki et al., ).…”
Section: Resultssupporting
confidence: 92%
“…The consumption of foods containing high concentrations of biogenic amines has been associated with health hazards [22]. High concentrations of certain amines in food may be interpreted as a consequence of poor quality of the raw materials used, contamination, or inappropriate conditions during food processing and storage [31].…”
Section: Resultsmentioning
confidence: 99%
“…The determination of biogenic amines and free amino acid fractions can provide useful information for the industry regarding freshness or spoilage and sanitary quality used as raw material for foods preparation. High concentrations of certain amines in food may be interpreted as a consequence of poor quality of the raw materials used, contamination, or inappropriate conditions during food processing and storage [31]. A number of swift and accurate analytical methods have been developed to determine biogenic amines levels in different foods.…”
Section: Analysis Of Biogenic Amines In Foodsmentioning
confidence: 99%
“…Among the most widely known foodborne toxicants, biogenic amines are a class of organic compounds formed through the decarboxylation of amino acids by microorganisms [3]. In particular, histamine, 2-(1H-imidazol-4-yl)ethanamine is a heterocyclic amine, synthesized from the microbial decarboxylation of the amino acid histidine [4]. Ingestion of sufficient quantities of histamine in food-typically in spoiled fish-is usually associated with "scombroid poisoning", a widely known foodborne intoxication [5].…”
Section: Introductionmentioning
confidence: 99%